UPAYA PENINGKATAN EFISIENSI PEMANFAATAN AIR EMBUNG DI NTT: STUDI KASUS EMBUNG OEMASI - KUPANG - Widiyono, Wahyu (Jurnal Hidrosfir Indonesia, 2010)
Effort to increase water used efficiency is one of the important aspect in the integrated embung management. The others are watershed and water storage management. Water used efficiency related, the first problem is how to deliver water from the embung storage to the water utilization area (village); and the second problem is how to use water for people consumption, cattle feeding and plant irrigation efficiently. Since theOemasi embung was built in 1991/1992 untill in 2010 some aspects were developed related to the increasing of people population in this area, i.e. developing of water tanks for people water consumption, cattle and irrigation; application of water used efficiency for cultivation of horticulture plants by using polybag potting system; and pipe network rehabilitation programme. The Oemasi embung problem and solution during the 20years of embung maintainance are the very valuable experience that can be used as a case study to manage 333 embungs that were built in the East Nusa Tenggara Province.